Spatial Analysis Of Human Capital Structures - Gajdos, Artur (Comparative Economic Research. Central and Eastern Europe, 2014)
The main purpose of this paper is to analyse the interdependence between labour productivity and the occupational structure of human capital in a spatial cross-section. Research indicates (see Fischer 2009) the possibility to assess the impact of the quality of human capital (measured by means of the level of education) on labour productivity in a spatial cross-section. This study attempts to thoroughly analyse the issue, assuming that apart from the level of education, the course of education (occupation) can also be a significant factor determining labour productivity in a spatial cross-section. The data used in this paper concerning labour force structure in major occupational groups in a regional cross-section comes from a Labour Force Survey. The data source specificity enables the assessment of labour force occupational specialisation at the regional level and the estimation of this specialisation at the subregional or county level. An in-depth analysis of the occupational structure of the labour market in a spatial cross-section is an important theoretical and practical area of study necessary for the development of effective labour market policies and the education system.